Household Durable Goods Spending in Urban Areas: A New Keynesian Micro Perspective - Mubarak, Munawwarah S.; Yunus, Amanus Khalifah Fil’ardy; Alfisyahrin, Ayu Latifah (International Journal of Economics and Financial Issues, 2024)
In the New Keynesian model, durable goods are typically assumed to be more responsive to monetary policy than non-durable goods. While this assumption is generally based on macroeconomic policy studies, this research aims to identify whether monetary authorities need to consider household microeconomic aspects such as dependents and long-term saving behavior when formulating policies to stimulate durable goods spending. The study employs two inverse semilogarithmic equations with micro data on urban households. Research findings confirm the existing assumption of the New Keynesian model. Durable goods spending remains sensitive to macroeconomic policies, particularly interest rate adjustments by monetary authorities. Furthermore, the research provides evidence supporting the life-cycle hypothesis for durable goods consumption among urban households. Therefore, this study underscores the pivotal role of durable goods expenditures in ensuring sustainable economic stability.